2017
DOI: 10.1088/1361-6560/aa93d2
|View full text |Cite
|
Sign up to set email alerts
|

Towards frameless maskless SRS through real-time 6DoF robotic motion compensation

Abstract: Purpose Stereotactic radiosurgery (SRS) uses precise dose placement to treat conditions of the CNS. Frame-based SRS uses a metal head ring fixed to the patient’s skull to provide high treatment accuracy, but patient comfort and clinical workflow may suffer. Frameless SRS, while potentially more convenient, may increase uncertainty of treatment accuracy and be physiologically confining to some patients. By incorporating highly precise robotics and advanced software algorithms into frameless treatments, we prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…In terms of patient perspectives, current literature cites FB procedures as invasive, anxiety-inducing, and potentially painful [4,[11][12][13]. In 2002, St George et al [14] contacted 47 patients 2-3 weeks post SRS and found that a third of them were still experiencing pain/numbness at the pin site.…”
Section: Comparisons To Current Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…In terms of patient perspectives, current literature cites FB procedures as invasive, anxiety-inducing, and potentially painful [4,[11][12][13]. In 2002, St George et al [14] contacted 47 patients 2-3 weeks post SRS and found that a third of them were still experiencing pain/numbness at the pin site.…”
Section: Comparisons To Current Literaturementioning
confidence: 99%
“…We prefer to avoid the term "frameless" as it is more accurate to describe a procedure by what it is rather than what it is not. In a FB procedure, a rigid frame is fixed to the patient's skull to suppress voluntary and involuntary movements under local anesthetic delivery and intravenous analgesia [4]. MB SRS, comparatively, utilizes a noninvasive thermoplastic custom-molded mask to the patient's face in order to immobilize the patient [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide variety of methods have been proposed for directly addressing such intrafractional motion. Among the most advanced, is the use of real-time patient motion compensation, where prior works include the use of a robotic arm to move a compact LINAC in sync with a tumor (Adler Jr, Chang, Murphy, Doty, Geis & Hancock 1997) Liu, Belcher, Grelewicz & Wiersma 2015, Belcher, Liu, Grelewicz, Kamil & Wiersma 2017. However, these methods typically employ a static treatment plan, and do not dynamically adapt this plan to real-time changes in patient anatomy.…”
Section: Introductionmentioning
confidence: 99%